SAIFI untuk Evaluasi Keandalan Sistem Distribusi Tenaga Listrik pada Jaringan Transmisi Menengah 20 KV - Febrianingrum, Annisa Larasati; Pramono, Subuh (Majalah Ilmiah Teknologi Elektro, 2022)
The Medium Voltage Network is an electrical power system between main substations and distribution substations with the scope from the out-going terminal of the power breaker to the in-coming separation / protection equipment for 20kV distribution transformer. The Medium Voltage Network distributes electricity and deals with customers must pay attention for the level of reliability which is able to supply electric power to consumers on a continuous basis. The reliability level of the distribution system can be determined by calculating SAIFI (System Average Interruption Frequency Index), which is the reliability index of the number of blackout frequencies. Based on the results of the calculation and analysis of the system-based reliability index that the obtained results of 10.89 times/customer/year with total energy not served was 57772 kWh which were considered unreliable distribution system according to the SPLN 68-2: 1986 index standard. Furthermore, it is necessary to analyze, evaluate the causes of trips and budget policies as an effort to reduce the value of SAIFI. Preventive activities include: routine inspections, installation of wire insulation, as well as utilizing IoT technology, databases and GPS for system digitization for distribution system reliability. Keyword: Medium voltage network, feeder, trip, reliability, SAIFI.